384 Characterization of Ex Vivo and In Vivo Intraoperative Neurosurgical Confocal Laser Endomicroscopy Imaging. (April 2023) - Xu, Yuan; Abramov, Irakliy; Mignucci-Jiménez, Giancarlo; Koskay, Grant; Belykh, Evgenii; Park, Marian; Eschbacher, Jennifer; Preul, Mark C.
Abstract : INTRODUCTION: The new FDA-cleared fluorescein sodium (FNa)-based confocal laser endomicroscopy (CLE) imaging system allows for intraoperative on-the-fly cellular level imaging. Two feasibility studies have been completed with intraoperative use of this CLE system in ex vivo and in vivo modalities. METHODS: Images acquired from two prospective CLE clinical studies, one ex vivo and one in vivo, were analyzed quantitatively. Two image quality parameters – brightness and contrast – were measured using Fiji software and compared between ex vivo and in vivo images for imaging timing from FNa dose and in glioma, meningioma, and intracranial metastatic tumor cases. The diagnostic performance of the two studies was compared. RESULTS: Overall, the in vivo images have higher brightness and contrast than the ex vivo images (p < 0.001). A weak negative correlation exists between image quality and timing of imaging after FNa dose for the ex vivo images, but not the in vivo images. In vivo images have higher brightness and contrast than ex vivo images acquired after FNa redosing. In vivo images have higher image quality than ex vivo images (p < 0.001) in glioma, meningioma, and intracranial metastatic tumor cases. In vivo imaging yielded higher sensitivity (90% vs. 72%) and negative predictive value (81% vs 38%) than ex vivo imaging. CONCLUSIONS: In our setting, in vivo CLE optical biopsy outperforms ex vivo CLE by producing higher quality images and less image deterioration, leading to better diagnostic performance. These results support the in vivo modality as the modality of choice for intraoperative CLE imaging.